2015
DOI: 10.2527/jas.2014-8593
|View full text |Cite
|
Sign up to set email alerts
|

Transcript profiles in longissimus dorsi muscle and subcutaneous adipose tissue: A comparison of pigs with different postweaning growth rates1

Abstract: Although most pigs recover rapidly from stresses associated with the transition of weaning, a portion of the population lags behind their contemporaries in growth performance. The underlying biological and molecular mechanisms involved in postweaning differences in growth performance are poorly understood. The objective of this experiment was to use transcriptional profiling of skeletal muscle and adipose tissue to develop a better understanding of the metabolic basis for poor weaned-pig transition. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…A previous study showed that light weaning weight piglets had a greater protein degradation rate and lower protein synthesis as well as reduced glucose metabolism compared with normal littermates [9]. The present result showed that IUGR piglets had greater serum tAA concentration than NBW piglets.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A previous study showed that light weaning weight piglets had a greater protein degradation rate and lower protein synthesis as well as reduced glucose metabolism compared with normal littermates [9]. The present result showed that IUGR piglets had greater serum tAA concentration than NBW piglets.…”
Section: Discussionsupporting
confidence: 58%
“…Skeletal muscles are the key components of growth and play important roles in many physiological activities, such as locomotion, postural maintenance, breathing, and thermogenesis [8,9]. Furthermore, skeletal muscles exhibit remarkable flexibility in the usage of fuel in response to the nutrient intake and energy demands of the organism's adaptation to a variety of conditions, including disease, stress, and reduced nutrient availability [9,10]. It has been well established that the physiological activity of skeletal muscle is mostly determined by the total fiber number and fiber type composition [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several RNA-seq studies have been reported in different tissues of pigs, such as the skeletal muscle[ 3 8 ], gonad[ 9 ], liver[ 10 , 11 ], adipose tissue[ 12 , 13 ], endometrium[ 14 ],which provided better understanding of the mRNA transcriptome in pig. MicroRNAs (miRNAs) play an important role in post-transcriptional regulation of metabolism in cells, such as β-cells, muscle cells, and adipocytes[ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…We performed validation of the relationship between lincRNA and their PTG in another longissimus dorsi muscle dataset, which contained 18 samples (NCBI GEO database, accession GSE65983) [ 38 ]. First, we calculated the expression of lincRNAs and their PTGs by HTSeq [ 39 ].…”
Section: Methodsmentioning
confidence: 99%